Strengthening Javanese literature material through the Novaja.id application as a form of Javanese cultural preservation - Fateah, Nur; Subhan, Subhan; Ifriza, Yahya Nur; Ninsiana, Widhiya (Universitas Mulawarman, 2025)
The preservation of regional languages, including Javanese, increasingly requires digital innovations that can support literacy development and sustain readers’ engagement. However, existing digital platforms for Javanese literary access often lack systematic development frameworks and user-centered design features, limiting their effectiveness and long-term usability. Responding to this gap, this study develops the Novaja.id Javanese Novel Library application through the integration of the System Development Life Cycle (SDLC) and User-Centered Design (UCD) methodologies. The research began with a user needs analysis conducted through surveys and in-depth interviews, which informed the design of an intuitive interface and optimized user experience. A prototype was subsequently tested through usability evaluations, and user feedback was incorporated into iterative refinements. The findings show that the final application meets user needs effectively, demonstrating high navigation ease, satisfactory feature performance, and stable and secure functionality. These outcomes indicate that combining SDLC and UCD enhances application quality and usability. Overall, Novaja.id has strong potential to expand access to Javanese literary works and contribute to Javanese language literacy and cultural preservation.